Differentiating Egyptian Entrepreneurs Small and Micro Business Owner-Managers According to the Entrepreneurial Traits - Zidan, Amr (The Arab Journal of Administration, 2023)
Purpose: to explore the entrepreneurial profile of the Egyptian entrepreneurs, small and Micro business owner-managers. The research, also, permit further understanding of entrepreneurial personality characteristics of the Egyptian entrepreneurs. Research Design: In this study, six traits, namely locus of control, independence, network, wealth valuation, optimism and innovativeness, are used to define the entrepreneurial profile of the Egyptian entrepreneurs. Six hypotheses were formed. The EFA and CFA were used. Entrepreneurial traits resulting from Factor analysis were examined according to MANOVA Test. Sample and Data: A convenience and judgemental sample of 607 Egyptian entrepreneurs and business owner-managers was selected from the Egyptian private sector population and a questionnaire was used for data collection. Findings: The research results indicated that the Egyptian Entrepreneurs and Owner- Managers have the following entrepreneurial traits, respectively: Wealth, Innovation, Network, Optimism, Independence, and Locus of control. The Egyptian Entrepreneurs and Owner-Managers have a paragmatic and realistic entrepreneurial personality. Originality: This study contributes to understanding the Egyptian entrepreneurial society. It also explores the paragmatic and realistic nature of the Egyptian entrepreneurs. Research Limitation/ Implication: Conclusions are limited by the non- propability sample (a convenience and judgemental sample). Rather, the results enforce the idea that psychological characteristics (trait approach) are still valid to portray the profile of the Egyptian entrepreneurial society. The results can be used by the Egyptian decision makers to articulate the entreepreneurial policies and entrepreneurship education programs.